Translation Strategies and Cultural Transfer in Ibrahim Al-Koni’s Tair an-Nahs az-zahabi - Maulana Ihsan Ahmad (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2025)
Purpose – This study aims to critique the Indonesian translation of Ibrāhīm Al-Kōnī’s short story Tair an-Nahs az-zahabi. It highlights the importance of preserving cultural and aesthetic integrity in literary translation, and evaluates the application of various translation techniques in transferring meaning from Arabic to Indonesian. Design/methods/approach –This research employs a qualitative descriptive method, focusing on comparative textual analysis between the source text and its Indonesian translation. The analysis centers on identifying and assessing translation techniques such as borrowing, calque, literal translation, transposition, modulation, amplification, reduction, adaptation, variation, discursive creation, clarification, and combinations thereof. Findings –The results show that techniques like borrowing and literal translation effectively retain core meanings, while methods such as modulation and amplification enhance clarity and emotional depth in the target text. However, certain techniques occasionally lead to slight shifts in meaning. Overall, the translation succeeds in conveying the symbolic, mythical, and cultural essence of the original story, albeit with some contextual reinterpretations. Research implications – The study underscores the need for a balanced use of translation strategies to maintain both literal and cultural fidelity in literary works. It suggests that a translator’s deep understanding of the source and target languages—along with their socio-cultural contexts—is essential for producing accurate and culturally resonant literary translations. These insights are valuable for translators and researchers seeking to improve the quality and sensitivity of Arabic–Indonesian literary translation.